Effect of MgO content on the quantitative role of hydrotalcite-like phase in a cement-slag system during carbonation. (November 2022) - Zhang, Yu; Liang, Minfei; Gan, Yidong; Çopuroğlu, Oğuzhan
Abstract: This paper reports the carbonation characteristics of a cement-slag system exposed to accelerated carbonation testing, and its improved carbonation resistance with the increasing MgO content in blast furnace slag, in which hydrotalcite-like phase plays a key role. Our research showed that the hydrotalcite-like phase started to carbonate upon contacting with the carbonate ions and bound more than 15 wt% CO2 −3 in the mildly carbonated and transition areas. This value was positively associated with the magnesia content of slag. Additionally, the proportion shared by hydrotalcite-like phase decreased in the fully carbonated area, and more CO2 was fixed in the form of calcium carbonate. Consistent with the thermodynamic modelling, the ratio of CO2 bound in carbonated hydrotalcite-like phase to the total CaCO3 continued to decrease as the CO2 ingress progressed. On the other hand, the reaction between hydrotalcite-like phase and CO2 was found to be volumetrically stable due to binding CO2 in the interlayer space, and Mg was still distributed within the original slag grain region. Mg/Al atomic ratio of hydrotalcite-like phase remained nearly the same before and after carbonation. Results of this study quantitatively emphasized the favorable effect of hydrotalcite-like phase to improve the carbonation resistance of slag-rich cementitious systems.